Operational Impact of ICTs in Front-Office of Selected Hotels in South-East and South-South Nigeria. (International Journal of Scientific Research and Management (IJSRM), 2017)
The operation of Front-Office of a hotel or a holiday centre is dependent on the effectiveness and efficiency of services rendered. When hotel services are predominantly manual, timely services may not be witnessed at all. But with the deployment of ICTs in front-office department of hotels services are rendered speedily and first impression of efficient service are created in the mind of the guest. This paper x-rayed the operational impact of deployment in front-office of selected hotels in South-east and South-South zone of Nigeria. The paper took an empirical study of selected hotels in the two zones, using a primary data collection technique via questionnaire to ascertain the level of deployment of ICTs in hotels and its operational effects in the service-delivery of concerned hotels. The result showed a concordance of the positive contribution of ICT in front-office with a Regression coefficient (R) of 0.841 (84.1%) coefficient of determination and the stated null hypotheses were rejected with sig. value of 0.000 alpha of 95% confidence interval. Therefore, it can be concluded that ICT is a positive contributor to efficiency in hotels and hospitality industries should encourage its installation and deployment